(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
ABSTRACT Hereditary multiple osteochondromatosis (HMO) is a rare familial bony disease largely diagnosed in early childhood. It is characterized by multiple bony outgrowths at the juxtaepiphyseal regions of long bones, or the surfaces of flat bones. Mutations in EXT 1 and EXT 2 genes are understood to be responsible for the pathogenesis of HMO. To highlight the importance of genetic counseling for affected individuals, we describe the case of a 21 years old female, who presented for the first time with clinically apparent multiple osteochondromas at various sites. The largest one found was at the back of the left knee. This particular osteochondroma caused discomfort and a degree of functional impairment, and was consequently surgically excised. Unusual to this case is that her two younger siblings, a brother and sister, were also discovered on examination to have multiple asymptomatic osteochondromas. All three children have osteochondromas around both knee joints in common. Genetic counseling is a vital platform for educating patients on the disease itself and its pattern of inheritance, so to reduce the risk of transmission of the defective trait to future generations.